(untitled) (Palíndromo, 2014)
The present work is a reflection on the digital art and the relationship established between the subject and his own body. To understand this relationship, which includes a social and philosophical view, we listed the important features of the history of modern art and its developments up to the digital art. The concept of subjectivity and corporality are incorporated to explain about the poetic proposal in the exhibition We Are The Art which will serve as a case study.